Financial feasibility and value engineering principles integrated quality function deployment for a manufacturing organization: A case study. Issue 1 (25th February 2014) - Rajiv, P.; Logesh, R.; Vinodh, Sekar; Rajanayagam, D.
Abstract : Purpose: – The purpose of this paper is to report a case study in which financial feasibility integrated quality function deployment (QFD) approach was implemented. Design/methodology/approach: – Customer complaints were systematically gathered. The house of quality (HoQ) matrix was developed. The technical descriptors were prioritized and subjected to the financial feasibility study. The cost calculations were carried out and the actions were derived. A set of value engineering (VE) principles was used during this case study. Findings: – The study reported in this paper indicated the need for integrating financial feasibility study with QFD for enhancing the effectiveness of the method. The measures taken to prevent the customer complaints will be of considerable value to the manufacturing organizations. Research limitations/implications: – During the conduct of case study, high-cost factors restricted the selection of materials which would exhibit higher performance. The case study was carried out in a single electronic switches manufacturing organization. Practical implications: – The manufacturing costs incurred have been reduced by incorporating changes in the part material. The outcomes of the study have been considered for further implementation in the case organisation which indicated the practicality of the study. Originality/value: – The concept of apportionment of HoQ cost developed with the idea of integrating the same with QFD is the original contribution of the authors.